ANALYSIS OF PROCIMATE ON THE CHARCOAL BRICKET AGRICULTURAL WASTE - Leni Rumiyanti; Annisa Irnanda; Yusup Hendronursito (Spektra: Jurnal Fisika dan Aplikasinya, 2018)
AbstractResearch has been conducted to know the best and worst quality of charcoal briquettes from agricultural wastes based on their proximate content. These agrarian wastes are rice husk, sugarcane baggage, cassava peel, corncob, and coconut shell. The research method is pyrolysis carbonization at 700-800 oC for 45 min and proximate analysis with techniques that suitable Indonesian National Standard (SNI) for testing of moisture, ash, volatile matter, and fixed carbon content. The research result showed that the best charcoal briquettes quality is cassava peel because it has the lowest water content of 0.3833% and the lowest ash content of 0.8452%. While the worst charcoal briquettes quality is corncob because it has the highest water content of 2,412% and the lowest fixed carbon of 71,442%.Keywords: charcoal briquettes, agricultural wastes, proximate analysis.